Immune response to arbovirus infection in obesity - Hameed, Muddassar; Geerling, Elizabeth; Pinto, Amelia K.; Miraj, Iqra; Weger-Lucarelli, James (Frontiers in Immunology, 2022)
Obesity is a global health problem that affects 650 million people worldwide and leads to diverse changes in host immunity. Individuals with obesity experience an increase in the size and the number of adipocytes, which function as an endocrine organ and release various adipocytokines such as leptin and adiponectin that exert wide ranging effects on other cells. In individuals with obesity, macrophages account for up to 40% of adipose tissue (AT) cells, three times more than in adipose tissue (10%) of healthy weight individuals and secrete several cytokines and chemokines such as interleukin (IL)-1β, chemokine C-C ligand (CCL)-2, IL-6, CCL5, and tumor necrosis factor (TNF)-α, leading to the development of inflammation. Overall, obesity-derived cytokines strongly affect immune responses and make patients with obesity more prone to severe symptoms than patients with a healthy weight. Several epidemiological studies reported a strong association between obesity and severe arthropod-borne virus (arbovirus) infections such as dengue virus (DENV), chikungunya virus (CHIKV), West Nile virus (WNV), and Sindbis virus (SINV). Recently, experimental investigations found that DENV, WNV, CHIKV and Mayaro virus (MAYV) infections cause worsened disease outcomes in infected diet induced obese (DIO) mice groups compared to infected healthy-weight animals. In this review article, we summarize the effects of obesity on the host immune response in the context of arboviral infections. We have outlined that obesity makes the host more susceptible to infectious agents, likely by disrupting the functions of innate and adaptive immune cells. We have also discussed the immune response of DIO mouse models against some important arboviruses such as CHIKV, MAYV, DENV, and WNV. We can speculate that obesity-induced disruption of innate and adaptive immune cell function in arboviral infections ultimately affects the course of arboviral disease. Therefore, further studies are needed to explore the cellular and molecular aspects of immunity that are compromised in obesity during arboviral infections or vaccination, which will be helpful in developing specific therapeutic/prophylactic interventions to prevent immunopathology and disease progression in individuals with obesity.